2011
DOI: 10.1186/cc10585
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with mortality in the medical intensive care unit

Abstract: IntroductionThe incidence of vitamin D deficiency in critically ill patients has been reported to range from as low as 17% to as high as 79%. Data regarding the relationship between 25-hydroxyvitamin D levels and outcomes in the medical intensive care unit are sparse. The goal of the study was to evaluate the prevalence of 25-hydroxyvitamin D deficiency in the medical intensive care unit and its relationship with outcomes.MethodThis was a retrospective study in a medical intensive care unit (MICU) at an inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
145
2
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 56 publications
17
145
2
8
Order By: Relevance
“…Recent studies have reported the incidence of vitamin D deficiency in intensive care patients to be 17%-82% (2,3). This is quite a wide range, and in this study we observed vitamin D deficiency in 77.9% of all patients.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Recent studies have reported the incidence of vitamin D deficiency in intensive care patients to be 17%-82% (2,3). This is quite a wide range, and in this study we observed vitamin D deficiency in 77.9% of all patients.…”
Section: Discussionsupporting
confidence: 53%
“…Calcitriol activates the vitamin D receptors in the cells, and this triggers the endocrine and autocrine effects of vitamin D. Vitamin D plays a major role in calcium homeostasis and bone metabolism, as well as in the immunoregulatory system (1). Vitamin D deficiency is defined as serum calcidiol levels below 25 ng mL -1 , and the incidence in intensive care patients varies between 17% and 82% (1)(2)(3). Reduced formation of calcitriol in the tissues might lead to impaired immune responses, mucosal barriers and endothelial Objective: Vitamin D is a fat-soluble vitamin that plays a major role in the regulation of bone and calcium metabolism and has effects on the immune and cardiovascular systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Moraes RB. et al and our study, Venkatram S. et al [44] suggested vitamin D levels under 10 ng/dl predicted hospital mortality in 83.6 % of their cohort. Gruson D et al suggested that 1,25 (OH)D and its ratio to PTH to be strongly and independently predict cardiovascular mortality in chronic heart failure [45].…”
Section: A) B)mentioning
confidence: 79%
“…The findings, reported by Amrein and colleagues [32], have revealed that the vast majority (87%) of ICU patients had low or very low concentrations of vitamin D, which was positively correlated with mortality. The study carried out by Venkatram and colleagues [33] demonstrated a correlation between the concentration of 25(OH)D in patients in a multi-specialized ICU and hospital mortality. Extremely low levels of vitamin D were found in 77% of patients.…”
Section: Significance Of Vitamin D In Icu Patientsmentioning
confidence: 99%